Polyion complex vesicles (PICsomes) from strong copolyelectrolytes. Stability and in vitro studies - Kwolek, Urszula; Nakai, Keita; Pluta, Anna; Zatorska, Maria; Wnuk, Dawid; Lasota, Sławomir; Bednar, Jan; Michalik, Marta; Yusa, Shin-Ichi; Kepczynski, Mariusz (Colloids and surfaces. B, Biointerfaces, 2017)
Polymer vesicles formed by a pair of oppositely charged diblock copolyelectrolytes (PICsomes) are considered as a good alternative to polymersomes formed by amphiphilic copolymers. Here, we report on inherent stability and in vitro biocompatibility of PICsomes prepared from a pair of oppositely charged zwitterionic-ionic copolymers, in which the ionic block is a strong polyelectrolyte. Our results demonstrated that the PICsomes are highly stable over a wide range of pH and temperatures. Direct microscopic observations revealed that the PICsomes retain their morphology in the presence of human serum. In vitro studies using human skin fibroblasts (HSFs) showed that the polymer vesicles are not cytotoxic and do not affect cell proliferation and adhesion. A model hydrophilic dye was effectively incorporated into the PICsomes by simple mixing. Using confocal microscopy observations, we demonstrated that the dye-loaded PICsomes are efficiently internalized by the cells and are located predominantly in endo/lysosomal compartments. Thus, the PICsomes have promising potential for use as nanocontainers for substances of biomedical interest.
Keywords: Polymers; Hydrophobic and Hydrophilic Interactions; buněčná adheze; proliferace buněk; Polyethylene Glycols; polyethylenglykoly; Cell Adhesion; polymery; elektronová kryomikroskopie; Cell Proliferation; hydrofobní a hydrofilní interakce; Cryoelectron Microscopy